2006
DOI: 10.1007/s00464-005-0634-3
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional learning curve in laparoscopy-assisted gastrectomy for early gastric cancer

Abstract: Background: Laparoscopy-assisted gastrectomy (LAG) is a complex and time-consuming procedure, which is increasingly used for early gastric cancer (EGC). We provide a multidimensional analysis of the learning curve in LAG. Methods: Cumulative sum method was used to analyze outcomes of 109 patients undergoing LAG for EGC by one surgeon over a two year period; the influence of patient selection was evaluated. Target failure rate was set at 10%, with failure defined as open conversion, mortality, major morbidity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
111
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(112 citation statements)
references
References 18 publications
1
111
0
Order By: Relevance
“…Therefore, a significant learning curve for LTG is associated with the mastering these operative techniques. Theoretically, ideal approaches for conducting statistical assessments of learning curves such as multivariate logistic regression or the cumulative sum (CUSUM) method have been used recently [13][14][15]. Commonly used outcomerelated variables, such as conversion to open surgery and the occurrence of severe complications, were also evaluated in the present study and were considered very useful for monitoring operative performance.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a significant learning curve for LTG is associated with the mastering these operative techniques. Theoretically, ideal approaches for conducting statistical assessments of learning curves such as multivariate logistic regression or the cumulative sum (CUSUM) method have been used recently [13][14][15]. Commonly used outcomerelated variables, such as conversion to open surgery and the occurrence of severe complications, were also evaluated in the present study and were considered very useful for monitoring operative performance.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that advanced procedures and extension of indications in LAG should be delayed until a learning curve is completed and the failure rate is less than for a multidimensional learning curve [12]. Therefore, a much larger number of cases is needed for a risk analysis of complications in LAG.…”
mentioning
confidence: 99%
“…In addition to this, they also showed better LND, faster oral intake, reduced pain, earlier hospital discharge, the same M/M and similar anastomotic leakage or stenosis, and similar LTS-DFS-OS compared to OG. As far as port site some Author has reported negative results [10][11][12][13][14] while other authors have noticed that the time is shorter and closer to open technique when a dedicated laparoscopic team perform at least 50 LG [4,5]. Recently, Haverkamp et al meta-analysis have showed the superiority of LG vs OG but oncological outcomes are still being debated [2,11].…”
Section: Discussionmentioning
confidence: 99%
“…In the past subtotal or total gastrectomy was always performed with open technique. In 1991 The Japanese school of gastric resection led by Professor Kitano performed the first Laparoscopic Subtotal Gastrectomy (LSG) for Early Gastric Cancer (EGC) [2][3][4][5][6][7][8]. Since this first reported surgery, Laparoscopic Gastrectomy (LG) has gained popularity in the last 20 years.…”
Section: Introductionmentioning
confidence: 99%